Essays by distinguished marketing scholars of the Society for Marketing Advances - Woodside, Arch G.; Moore, Ellen M. (Advances in business marketing and purchasing ;, 2002)
This volume presents a collection of papers written by senior marketing scholars based on their presentations upon receiving the 'Society for Marketing Advances Distinguished Marketing Scholar Award'. Each paper reviews a stream of research in marketing and reflects the wisdom of authors highly cited in the literature - with citations of their work usually spanning several decades.